2013
DOI: 10.1109/jtehm.2013.2271898
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Alternate Combination of “Error-Enhancing” and “Active Assistive” Robot-Mediated Treatments on Stroke Patients

Abstract: This paper aimed at investigating the effects of a novel robotic-aided rehabilitation treatment for the recovery of the upper limb related capabilities in chronic post stroke patients. Eighteen post-stroke patients were enrolled in a six-week therapy program and divided into two groups. They were all required to perform horizontal pointing movements both in the presence of a robot-generated divergent force field (DF) that pushed their hands proportional to the trajectory error and perpendicular to the directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 53 publications
(61 reference statements)
0
25
0
Order By: Relevance
“…Research on motor learning has emphasized that errors are fundamental signals that drive motor adaptation [6], [7], [8], [9]. Thereby, there has been a progression in the development of training strategies that amplify movement errors rather than decrease them [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on motor learning has emphasized that errors are fundamental signals that drive motor adaptation [6], [7], [8], [9]. Thereby, there has been a progression in the development of training strategies that amplify movement errors rather than decrease them [1].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, there has been a progression in the development of training strategies that amplify movement errors rather than decrease them [1]. In patients with chronic stroke, amplifying errors with a robotic force field during reaching resulted in straighter movements when the force field was removed [7], [9]. Increasing limb phasing error in post-stroke participants' gait through a split-belt treadmill induced a long term increase in walking symmetry [8].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 (EA only), Table 2 (ER only) and Table 3 (EA and ER) described all 13 studies as well as their results. Among the 13 selected studies, there are six randomized controlled trials (RCT) [ 52 57 ], five crossover studies [ 52 , 54 , 58 – 60 ], one quasi-experimental study [ 24 ], two randomized comparative study [ 61 , 62 ] and one pilot study [ 63 ]. Among all thirteen studies, only four could be found in clinical trials registry [ 52 , 56 , 57 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The different between EA and ER groups was significant [F(1,13) = 4.29, p < 0.001]. Stroke subjects showed less adaptation capacity than healthy subjects (26% less) Initial direction error: 1.53 (very large effect) 1/10, poor quality Tropea et al [ 54 ] Crossover randomized controlled trial. Trial not registered 18 in total EA = 9 ER = 9 (before cross-over) Ages: 21–71 (EA: mean = 49.7± 18.7; ER: mean = 44.9 ± 15.9), 9 males and 9 females, all participants suffered from a chronic stroke (mean/SD unknown), CM: First EA group: mean = 4.9 ± 0.9 First ER group: mean = 4.2 ± 1.0 InMotion2 robotic system Experimental tasks: reaching targets in a plane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation